Comparison between dynamic mechanical properties of dam and sieved concrete under biaxial tension-compression. (1st February 2017) - Shen, Lu; Wang, Licheng; Song, Yupu; Shi, Linlin
Highlights: The dynamic biaxial T-C test data of dam and sieved concrete were obtained and compared. Combined effects of stress ratio and strain rate on properties of dam concrete were investigated. Dynamic biaxial T-C failure criterion of dam and sieved concrete is established. Abstract: A comparative study on the dynamic properties of dam and sieved concrete was conducted based on dynamic biaxial tensile-compressive tests. Specimens were designed to be prismatic shape with a size of 250 × 250 × 400 mm for dam concrete and 150 × 150 × 300 mm for sieved concrete, respectively. Each specimen was biaxially loaded by constant tensile-compressive (T-C) stress ratios (0:−1, 0.05:−1, 0.1:−1, 0.25:−1, 0.5:−1, and ∞) at the strain rate of 10 −5  s −1, 10 −4  s −1, 10 −3  s −1, and 10 −2  s −1 by a servo-hydraulic multi-axial testing machine. The failure modes of specimens have been compared under various biaxial T-C loading conditions at each strain rate, thus the fracture surface of sieved concrete specimen is smoother than dam concrete. The dynamic strength of dam concrete is lower than sieved concrete under the same loading condition, and the ratio of them is insensitive to strain rate. The growth rates of dynamic strength for dam concrete is consistent with sieved concrete, whereas much larger than ordinary concrete. By regression of the test results, the dynamic T-C failure criterions for dam and sieved concrete were proposed after considering the combined effects of strain rate and stress ratio.